1970
DOI: 10.1104/pp.45.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the Auxin Response in Etiolated Pea Stem Sections

Abstract: The short term growth response of etiolated pea stem segments (Pisum sativum L., var. Alaska) was investigated with the use of a high resolution growth-recording device. The immediate effect of treatment with indole-3-acetic acid is an inhibition of growth. This inhibition lasts about 10 minutes, and then the rate of elongation rises abruptly to a new steady rate about 4 times the rate of elongation before auxin treatment. This rapid steady rate of elongation, however, continues for only about 25 minutes befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1971
1971
1980
1980

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…it suggests that the ethylene-producing system requires continued synthesis of a protein, as suggested in the case of growth by Barkley and Evans (3,11,12). They proposed that the primary action of auxin in growth does not involve synthesis of a certain specific protein coupled to the growth process, for the lag period of the auxin stimulation is relatively short (10 min), and cycloheximide, and actinomycin D pretreatments do not significantly affect its length.…”
Section: Auxin-induced Etirmentioning
confidence: 94%
“…it suggests that the ethylene-producing system requires continued synthesis of a protein, as suggested in the case of growth by Barkley and Evans (3,11,12). They proposed that the primary action of auxin in growth does not involve synthesis of a certain specific protein coupled to the growth process, for the lag period of the auxin stimulation is relatively short (10 min), and cycloheximide, and actinomycin D pretreatments do not significantly affect its length.…”
Section: Auxin-induced Etirmentioning
confidence: 94%
“…It has been shown that inhibitors of protein synthesis have a rapid effect on IAA-induced growth (1,5,9,13,16,19). This has led to the suggestion that an unstable protein, which has been called growth-limiting protein (5), is necessary for auxin-induced cell expansion.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that there is a sizeable growth promotion by auxin after protein synthesis has essentially ceased. It is concluded that the initial phases of auxin action do not require protein synthesis but that its action depends on the existing pool of growth-limiting proteins which is rapidly depleted, and protein synthesis is then required for continued elongation.It has been shown that inhibitors of protein synthesis have a rapid effect on IAA-induced growth (1,5,9,13,16,19). This has led to the suggestion that an unstable protein, which has been called growth-limiting protein (5), is necessary for auxin-induced cell expansion.…”
mentioning
confidence: 99%
“…There is precedent for interaction of auxin hormones with the plasma membrane (4, 17). The latter findings (4) form a basis for integration of the seemingly disparate fast reactions of auxin action (1,3,12,16) and the delayed transcriptional responses (7,8,11) into a postulated mechanism involving a single master reaction (15). This study provides evidence from high resolution electron microscopy which, in conjunction with fluorescence probe experiments of the accompanying paper (5) were soaked in water overnight, planted in moist vermiculite, and germinated in the dark at 29 C in a constant temperature, high humidity chamber (4).…”
mentioning
confidence: 99%